The Impact of Organizational Agility on Job Engagement at Agricultural Companies in Gadarif State- Sudan - Farah, Farah Yassein; Badawi, Mamoun Yassin; Babeker, Safa Yasser (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to know the impact of the Organizational Agility on the Job Engagement; the study followed the analytical descriptive method, and a questionnaire was designed and distributed to a sample of (60) employees at the (10) agricultural companies in Gadarif State in the Sudan. The study found that, the practices of organizational agility and job engagement were high, also, the results showed statistical significant impact of the organizational agility (acting agility and decision- making agility) on the job employment. The study offered a set of recommendations to help decision- makers of the companies to build and enhance the organizational agility as a catalyst for the job engagement of human resources.